Chemical Immunology and Allergy 2005
DOI: 10.1159/000087569
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidants in Mast Cell Activation

Abstract: Reactive oxygen species (ROS), such as superoxide, hydrogen peroxide (H2O2), and hydroxyl radical, have for a long time been considered as accidental by-products of respiratory energy production in mitochondria and as being useless and rather deleterious to biological systems. Contrary to such a classical view, accumulating evidence indicates that upon stimulation of divergent receptor systems, ROS are intentionally produced and even required for appropriate signal transduction and biological responses. Work b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 39 publications
3
57
1
4
Order By: Relevance
“…A possible mechanism by which ET-1 receptor antagonism could mediate effects over cardiac mast cell density or activation is through the reduction of myocardial oxidative stress. In vitro studies have identified reactive oxygen species as an initiator of mast cell cytokine expression and histamine release (50,52). Recent work by Gilles et al (24) demonstrated a role for oxidative stress in mast cell activation in vivo following ischemia and reperfusion.…”
Section: Effect Of Et a Receptor Antagonism On Postfistula Remodelingmentioning
confidence: 99%
“…A possible mechanism by which ET-1 receptor antagonism could mediate effects over cardiac mast cell density or activation is through the reduction of myocardial oxidative stress. In vitro studies have identified reactive oxygen species as an initiator of mast cell cytokine expression and histamine release (50,52). Recent work by Gilles et al (24) demonstrated a role for oxidative stress in mast cell activation in vivo following ischemia and reperfusion.…”
Section: Effect Of Et a Receptor Antagonism On Postfistula Remodelingmentioning
confidence: 99%
“…The findings from that study showed corresponding increases in mast cell secretory products (i.e., histamine or TNF-␣) and elevated myocardial oxidants. Furthermore, in vitro studies have identified intracellular reactive oxygen species as the initiator of mast cell cytokine expression and histamine release (2,40,44). Recent reports have demonstrated that treatment of ischemic myocardium with either selective (ET A , BQ-123) or nonselective (ET A /ET B , bosentan) receptor antagonism significantly reduced catalase and superoxide dismutase activity as well as glutathione content (21,36).…”
Section: Mast Cell Density Postfistulamentioning
confidence: 99%
“…75 Mast cells are activated by oxidized LDL 76 and reactive oxygen species. 77 T lymphocytes in atherosclerotic plaques also express matrix metalloproteinases. 50 T lymphocytes are activated by oxidized LDL, 78 inflammatory cytokines, 79 and interaction with adhesion molecules.…”
Section: Leukocytesmentioning
confidence: 99%